Application of monoclonal antibodies in diabetes: A bibliometric analysis from 2004–2024 - Rui Wei; Bochao Jia; Shuang Zheng; Xuexue Zhang; Miaoran Wang; Ning Sun; Rui Zhang; Qiuyan Li (Human Vaccines & Immunotherapeutics, 2025)
Monoclonal antibodies (mAbs) have shown significant promise in diabetes treatment through immunobiological mechanisms. To comprehensively understand the current development status and future trends of this research field, this study used bibliometric methods to retrieve literature data from the Web of Science Core Collection database from 2004 to 2024 and conducted a comprehensive analysis using R software and VOSviewer. A total of 900 papers were published by 4,678 authors from 56 countries, with global publication volume and average citation frequency peaking in 2019, after which the field entered a stable development phase. The United States emerged as the leading contributor in terms of total publications, citations, and national collaborations. The journal Diabetes had the highest publication output. Herold KC from Yale University ranked highest in publication count, citation frequency, and Hirsch index. Four key research focuses were identified in T1D: the multifaceted roles of mAbs in clinical trials (a hot mature topic), developing therapeutic targets through animal models (a centralized, declining topic), inducing immune tolerance in transplantation using mAbs (a mature, declining topic), and assessing the safety, risk, and efficacy of mAbs in diabetes treatment (a niche and well-developed topic). Substantial clinical progress has already been achieved with mAbs targeting autoimmune destruction in T1D, while therapeutic strategies for metabolic dysregulation in T2D are primarily in the preclinical stage yet show promising potential. Advancing combination therapies, personalizing treatments, and enhancing mechanistic research will improve the safety and efficacy of mAbs in diabetes management, providing valuable insights for future research in this field.